Rola tekstów o charakterze religijnym XVIII wieku w poznaniu żywego języka ruskojęzycznej ludności dawnej Rzeczypospolitej (na materiale tekstu Bohosłowija nrawouczytelnaja, Poczajów 1751) - Getka, Joanna (Acta Polono-Ruthenica, 2019)
The purpose of this article is to present the role of religious texts in the analysis of common language of the people of the former Commonwealth of the Two Nations. The subject of the analysis is the text Bohoslowija nrawouczytelnaja... published in the basilian’s printing house in Pochayev in 1751. Textual features of living Ukrainian language (approximation of articulation [i] and [y], hardness [t] and [d], morphological features) are common tendencies, and can be a testimony of the state of the Ukrainian language of the eighteenth century. The analysis supports the thesis of evolutionary development of Ukrainian written language.